Transportasi Jamaah Haji Masa Kolonial Abad XIX - Iin Hindasah; Amung Ahmad Syahir Muharam (UIN Sunan Gunung Djati Bandung, 2018)
The Hajj during the colonial period experienced its own challenges in addition to transportation to Mecca which was not easy. Pilgrims were also faced with the hajj policy which burdened pilgrims. This study aims to find out how the pilgrimage transportation in the colonial period, especially the nineteenth century, both in terms of health services and also the condition of the ship during the voyage. The method used in this study is a qualitative method, namely by collecting data through literature and documentation. Data analysis techniques are carried out with heuristic methods, criticism, interpretation and historiography. The results of this study indicate that the Dutch East Indies government provided transportation facilities for Indonesian pilgrims at that time only for economic and political purposes. Hajj policies were made to suppress the increasing number of pilgrims and also to monitor pilgrims so as not to disrupt the political legitimacy of the colonial government in the Dutch East Indies. Transportation of pilgrims on the 19th century is using a sailing ship which later in the mid-19th century was replaced by a steamship. The Colonial Government paid little attention to aspects of health services and passenger comfort on board during the voyage.